Evaluación de enmiendas orgánicas: efectos en la producción y fitosanidad del cacao (theobroma cacao l.) cultivar ccn-51 - Noles Leon, Mercedes Johanna (Machala : Universidad Técnica de Machala, 2020)
Cocoa is a tropical fruit of great economic importance for all the countries that produce it, through its production it generates employment directly and indirectly throughout its production chain. Ecuador is the fourth largest exporter of cocoa beans in the world and due to its organoleptic characteristics it leads the production of fine and aromatic cocoa in international markets. At a national level, among the main provinces that produce cocoa is the province of El Oro, which has the appropriate climatic conditions that allow it to develop its productive potential to the maximum, increasing the profitability of the crop and therefore guaranteeing a good economy for the producer. The negative side is the indiscriminate use of agrochemicals that degrade the soil, contaminate the water and put people's health at risk. This is why a proposal has arisen to counteract the negative factors by applying biochar and solid mountain microorganisms in combination with other organic amendments in order to improve the production and phytosanitary conditions of the CCN-51 cocoa crop, which is an early hybrid with high productivity. The present research was developed in the Rio Negro Site of La Victoria Parish, belonging to Santa Rosa County. The experimental design was proposed in completely randomized blocks with six treatments and one control each with ten repetitions: T1: Biocarbon (100g) + (50g) of solid mountain microorganisms; T2: Biocarbon (100g) + Fossil Shel Fluor (5g) + (50g) of solid mountain microorganisms; T3: Biocarbon (50g) + Fossil Shel Fluor (10g) + (50g) of solid mountain microorganisms; T4: Fossil Shel Fluor (10g) + (50g) of Solid Mountain Microorganisms; T5: Calcium Silicate (50g)) + (50g) of Solid Mountain Microorganisms; T6: Agricultural Lime (50g) + Biocoal (50g) + (50g) of Solid Mountain Microorganisms. The variables evaluated were: number of ears per plant (NMP), number of healthy ears (NMS), number of diseased ears (NME), ear weight (PM), fresh seed weight (PSF), number of seeds per ear (NSM), seed dry weight (PSS), ear index (IM), seed index (IS), husk index (CI), percentage of good fermentation (FB), percentage of medium fermentation (FM), percentage of slate fermentation (PF), percentage of violet fermentation (FV), percentage of mold fermentation (FMH), percentage of humidity (PDH) and yield (RTO). The data obtained were analyzed with the SPSS statistical software using the one-factor ANOVA and the Tukey test (∝=0,05). The results obtained indicate that it is very profitable to apply biocoal in combination with solid mountain microorganisms to promote the availability of the necessary nutrients for plant development. The organic amendments based on silicon strengthen the cell wall thus generating resistance to the plant against the attack of pests and diseases, also reduces water stress allowing you to have an increase in their performance which translates into profits for the farmer. In the one-factor ANOVA test it shows that there is significant difference for the NMS, NME, IM, PDH and RTO variable. The T1 and T2 with (59.10 and 53.59 qq/ha/year) respectively show the highest averages in production and also the best phytosanitary condition, leaving evidence that biochar enhances the effect of organic amendments that accompany it, also improves soil health when applied in an edaphic way and increases the reserve of nutrients in the root zone of the plant, which facilitates the absorption for an optimal production. T4 obtained the lowest average in RTO, NMP and NMS. In the cutting test to evaluate the physical quality of the almonds, the highest percentage of good fermentation (BF) obtained T4 (92.6%), which indicates that it is within the range allowed by the chocolate industry, however it obtained (0.9%) of HF; the Control obtained (9.5%) in medium fermentation (MF); FP the Control with (0.3%); VF the Control with (1.2%). In conclusion, the application of biochar + MMS improves the production and phytosanitary of the crop and has a low nutritional cost per hectare of $ 113.32 and a benefit of $ 4725.5 compared to other treatments demonstrating that these two amendments are effective and low cost to be applied in a cocoa plantation.
El cacao es un fruto tropical de gran importancia económica para todos los países que lo producen, mediante su producción genera empleo de forma directa e indirecta a lo largo de toda su cadena productiva. Ecuador ocupa el cuarto lugar como exportador de cacao en grano a nivel mundial y por las características organolépticas que posee lidera la producción de cacao fino y de aroma en los mercado internacionales. A nivel nacional entre las principales provincias que lo producen se encuentra la provincia de El Oro que cuenta con las condiciones climáticas adecuadas que le permiten desarrollar al máximo su potencial productivo aumentando la rentabilidad del cultivo y por lo tanto garantiza una buena economía al productor. Lo negativo se encuentra en el uso indiscriminado de agroquímicos que degradan el suelo, contaminan el agua y pone en riesgo la salud de las personas, es por esto que surge una propuesta para contrarrestar los factores negativos mediante la aplicación edáfica de biocarbón y microorganismos de montaña sólidos en combinación con otras enmiendas orgánicas con el objetivo de mejorar la producción y fitosanidad del cultivo de cacao CCN-51, que es un hibrido precoz y de alta productividad. La presente investigación se desarrolló en el Sitio Rio Negro de la Parroquia La Victoria perteneciente al Cantón Santa Rosa, el diseño experimental que se planteo fue bloques completamente al azar con seis tratamientos y un testigo cada uno conto con diez repeticiones: T1: Biocarbón (100g) +(50g) de Microorganismos de montaña sólidos; T2: Biocarbón (100g) + Fossil Shel Fluor (5g) + (50g) de Microorganismos de microorganismos sólidos; T3: Biocarbón (50g) + Fossil Shel Fluor (10g) + (50g) de Microorganismos de montaña sólidos; T4: Fossil Shel Fluor (10g) + (50g) de Microorganismos de montaña sólidos; T5: Silicato de Calcio (50g)) + (50g) de Microorganismos de montaña sólidos; T6: Cal agrícola (50g) + biocarbón (50g) + (50g) de Microorganismos de montaña sólidos. Las variables evaluadas fueron: número de mazorcas por planta (NMP), numero de mazorcas sanas (NMS), numero de mazorcas enfermas (NME), peso de mazorca (PM), peso de semilla en fresco (PSF), numero de semillas por mazorca (NSM), peso seco de las semillas (PSS), índice de mazorca (IM), índice de semillas (IS), índice de cascarillas (IC), porcentaje de fermentación buena (FB), porcentaje de fermentación media (FM), porcentaje de fermentación pizarra (FP), porcentaje de fermentación violeta (FV), porcentaje de fermentación con moho (FMH), porcentaje de humedad (PDH) y rendimiento (RTO). Los datos obtenidos se analizaron con el software estadístico SPSS mediante el ANOVA de un factor y la prueba de Tukey (∝=0,05). Los resultados obtenidos señalan que es muy rentable aplicar el biocarbón en combinación con los microorganismos de montaña sólidos para favorecer la disponibilidad de los nutrimentos necesarios para el desarrollo de la planta. Las enmiendas orgánicas a base de silicio fortalecen la pared celular por lo tanto generan resistencia a la planta contra el ataque de plagas y enfermedades, también disminuye el estrés hídrico permitiéndole tener un incremento en su rendimiento lo que se traduce en ganancias para el agricultor. En la prueba de ANOVA de un factor muestra que existe diferencia significancia para la variable NMS, NME, IM, PDH Y RTO. El T1 y T2 con (59,10 y 53,59 qq/ha/año) respectivamente muestran las medias más altas en producción y también el mejor estado fitosanitario dejando en evidencia que el biocarbón potencia el efecto de las enmiendas orgánicas que lo acompañan, además mejora la salud del suelo al ser aplicados de forma edáfica e incrementa la reserva de nutrientes en la zona radicular de la planta, lo que facilita la absorción para una óptima producción. El T4 obtuvo la media más baja en RTO, NMP y NMS. En la prueba de corte para evaluar la calidad física de las almendras el mayor porcentaje de fermentación buena (FB) obtuvo el T4 (92,6%), lo que indica que se encuentra en el rango permitido por la industria chocolatera, sin embargo obtuvo el (0,9%) de FMH; el Testigo obtuvo el (9,5%) en fermentación media (FM); FP el Testigo con (0,3%); FV el Testigo con (1,2%). Para concluir, la aplicación de biocarbón + MMS mejora la producción y fitosanidad del cultivo además tiene un bajo costo nutricional por hectárea de $ 113,32 y un beneficio de $4725,5 en comparación con los otros tratamientos demostrando que estas dos enmiendas son efectivas y de bajo costo para ser aplicadas en una plantación de cacao.
Keywords: BIOCARBÓN; MICOORGANISMOS; CACAO; PRODUCCIÓN